Li2B12 and Li3B12: Prediction of the Smallest Tubular and Cage‐like Boron Structures - Dong, Xue; Jalife, Said; Vásquez‐Espinal, Alejandro; Ravell, Estefanía; Pan, Sudip; Cabellos, José Luis; Liang, Wei‐yan; Cui, Zhong‐hua; Merino, Gabriel (Angewandte Chemie International Edition, 2018)
An intriguing structural transition from the quasi‐planar form of B12 cluster upon the interaction with lithium atoms is reported. High‐level computations show that the lowest energy structures of LiB12, Li2B12, and Li3B12 have quasi‐planar (Cs), tubular (D6d), and cage‐like (Cs) geometries, respectively. The energetic cost of distorting the B12 quasi‐planar fragment is overcompensated by an enhanced electrostatic interaction between the Li cations and the tubular or cage‐like B12 fragments, which is the main reason of such drastic structural changes, resulting in the smallest tubular (Li2B12) and cage‐like (Li3B12) boron structures reported to date. Let's play with a charge transfer tool! The energetic cost of distorting the B12 quasi‐planar fragment in Li2B12 and Li3B12 is overcompensated by an enhanced electrostatic interaction between the Li cations and the tubular or cage‐like B12 fragments. This is the main reason of a drastic structural changes in the B12 core, resulting in the smallest reported tubular (Li2B12) and cage‐like (Li3B12) boron structures.